Does dispersal capacity matter for freshwater biodiversity under climate change?. (5th December 2016) - Bush, Alex; Hoskins, Andrew J.
Summary: Freshwater ecosystems appear to be sensitive to even minor climatic shifts, and the dendritic nature of rivers as well as patchy distribution of habitats within the terrestrial landscape could limit the ability of species to track suitable climate conditions. Although the importance of dispersal is recognised in theory, there is great uncertainty when quantifying the capacity of species to shift their distributions in response to climate change. The influence of dispersal capacity on species' vulnerability to climate change was assessed, using the modelled projections of 527 freshwater species in New South Wales (NSW), Australia. Species' future ranges were calculated by iteratively identifying colonisation of accessible habitats and loss of suitable habitats within network models. The accessibility of new habitats was based on a given dispersal mode (aquatic, semi‐terrestrial and aerial). The relative impact of dispersal parameters on projected range were evaluated alongside other known sources of uncertainty (climate and emissions scenarios, modelling algorithm and biological group), analysed collectively in a generalised additive mixed‐model, and spatially to locate regions of NSW where projections are associated with the most uncertainty. Our simulations (1.4 million scenario combinations) suggest at least a third of species will lose more than half their range under climate change. Nevertheless, we emphasise the broad uncertainty that any average encapsulates. Dispersal capacity only had a minor impact on projected range shifts relative to other modelling assumptions but the network‐pathways and maps of uncertainty have value for conservation planning at large scales. Projected range losses initially decreased rapidly as dispersal rates increased but the benefits are reduced above 2–3 km year −1 . Taxa restricted to dispersal within the stream network (aquatic) were more vulnerable to climate change than taxa with semi‐terrestrial or aerial dispersal and maps of variation due to dispersal mode and rate indicate where habitat connectivity would be most beneficial. This study demonstrates the breadth of uncertainties that challenge plans for improving ecosystem adaptation under climate change and highlights where in the landscape those differences were consistent. We emphasise the need for freshwater conservation studies to be ecologically representative, to focus on broad‐scale connectivity for taxa that can move between catchments, and an accessible network of refugia for taxa with more limited dispersal.